2016
DOI: 10.1515/hsz-2015-0295
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 activation in the treatment of neurodegenerative diseases: a focus on its role in mitochondrial bioenergetics and function

Abstract: Abstract:The nuclear factor erythroid-derived 2 (NF-E2)-related factor 2 (Nrf2) is a transcription factor wellknown for its function in controlling the basal and inducible expression of a variety of antioxidant and detoxifying enzymes. As part of its cytoprotective activity, increasing evidence supports its role in metabolism and mitochondrial bioenergetics and function. Neurodegenerative diseases are excellent candidates for Nrf2-targeted treatments. Most neurodegenerative conditions such as Alzheimer's disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 150 publications
(178 reference statements)
4
87
0
Order By: Relevance
“…This has since been confirmed in in vivo studies [48]. What we have been interested in establishing is a more direct involvement of Nrf2 in modulating mitochondrial function (recently reviewed in 7, ∗8, 10). We showed that respiration and ATP levels are decreased in cells and mitochondria isolated from Nrf2-knockout (Nrf2-KO) mice, while they are increased in their Keap1-knockout (Keap1-KO) and Keap1-knockdown (Keap1-KD) counterparts ∗∗49, 50.…”
Section: Nrf2 and Mitochondrial Homeostasismentioning
confidence: 80%
See 2 more Smart Citations
“…This has since been confirmed in in vivo studies [48]. What we have been interested in establishing is a more direct involvement of Nrf2 in modulating mitochondrial function (recently reviewed in 7, ∗8, 10). We showed that respiration and ATP levels are decreased in cells and mitochondria isolated from Nrf2-knockout (Nrf2-KO) mice, while they are increased in their Keap1-knockout (Keap1-KO) and Keap1-knockdown (Keap1-KD) counterparts ∗∗49, 50.…”
Section: Nrf2 and Mitochondrial Homeostasismentioning
confidence: 80%
“…Neurodegenerative disorders are commonly characterized by oxidative stress, mitochondrial dysfunction and protein misfolding, making them ideal targets for Nrf2 activator mediated therapy (reviewed in 10, 65, 66). Nrf2 activation has long been shown to be cytoprotective in both toxicological as well as genetic models of neurodegeneration in vitro and in vivo ∗67, 68, ∗69, ∗70, 71, ∗72, 73, 74, 75, ∗∗76.…”
Section: Nrf2 Mitochondrial Function and Neurological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, studies into Nrf2 function exposed a plethora of cellular processes other than cytoprotection which are regulated by its signaling. These include diabetes [96], cancer cell growth and chemoresistance [97][98][99], neurodegenerative diseases [100], redox homeostasis in the aging heart [101], as well as oxidative stress and inflammatory pathways [102]. Furthermore, ROS are generated as by products during inflammation in the gut epithelia, primarily due to respiratory burst activity from phagocytes described earlier in this review.…”
Section: Cytoprotection By Lactobacilli-activation Of Keap1/nrf2/are mentioning
confidence: 94%
“…620,621 The latter aspect has been harnessed in chemotherapy in which specific pharmaceuticals have been developed to inhibit Nrf2 activity in cancer cells, since it is now known that cancer cells too can take advantage of the cytoprotective properties of Nrf2 activation. 622,166 Pharmaceutical Nrf2 activation in non-cancer cases must be equally considered with caution; the failed Bardoxolone methyl trial 561 in patients with chronic kidney disease acts as stark warning that attempting to exceed normal physiological limits can have serious and sometimes fatal consequences.…”
Section: Dose Considerationsmentioning
confidence: 99%